2010
DOI: 10.1159/000319754
|View full text |Cite
|
Sign up to set email alerts
|

Aquagenic Wrinkling of the Palms in an Adult Cystic Fibrosis Population

Abstract: Background: Aquagenic wrinkling of the palms (AWP) is a rare condition characterised by the development of oedema and excessive wrinkling of the palms following exposure to water. It has frequently been associated with cystic fibrosis (CF). Early reports of AWP have only been case reports or small case series; there has only been one reported prevalence study of AWP in a CF population. Objective: To determine the incidence and characteristics of AWP in the adult CF population in Northern Ireland. Methods: 105 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…It has been proposed that in patients with CF and hyperhidrosis, the elevated epidermal sodium content might increase the absorption of water above levels of healthy persons [9,10]. In general, it is assumed that in AWP patients structural changes in the stratum corneum result in a malfunction following water contact, and an aberrant expression of AQP5, which belongs to the aquaporin water channel family, was shown in the sweat glands of AWP patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that in patients with CF and hyperhidrosis, the elevated epidermal sodium content might increase the absorption of water above levels of healthy persons [9,10]. In general, it is assumed that in AWP patients structural changes in the stratum corneum result in a malfunction following water contact, and an aberrant expression of AQP5, which belongs to the aquaporin water channel family, was shown in the sweat glands of AWP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Berk et al [14] demonstrated that CF patients who were ΔF508 homozygous had severer wrinkling than those with other CF genotypes. In addition, a survey-based study showed that 41% of CF patients admitted to having AWP [15]. Finally, Arkin et al [16] found that 84% of CF patients demonstrated AWP, in contrast to none of the controls.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of AWP in CF is however unclear (it varies from 41 to 84%) as the methods of evaluation are neither homogeneous nor validated in large, stringent case-control studies [15,16]. Moreover, AWP has been reported even in otherwise healthy individuals as well as in patients with marasmus [10], atopic dermatitis, hyperhidrosis and in patients taking selective cyclooxygenase (COX-2) inhibitors, angiotensin-converting enzyme inhibitors, nonsteroidal anti-inflammatory drugs and antibiotics [12,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study highlighted a 41% incidence of aquagenic wrinkling of the palms in 105 patients with CF. The authors suggested that homozygosity for the F508del CFTR (cystic fibrosis transmembrane conductance regulator) mutation may predispose to aquagenic wrinkling of the palms [8]. A clinical trial showing the decreased time interval for aquagenic wrinkling using the water immersion test in patients with CF (2 min) compared with a heterozygous mutation (carrier) group (7 min) and control group (14 min) also strengthens the relationship between ASA and CF [9].…”
Section: Discussionmentioning
confidence: 99%